Absence of the Adenosine A2A Receptor Confers Pulmonary Arterial Hypertension Through RhoA/ROCK Signaling Pathway in Mice. Issue 6 (December 2015) - Shang, Ping; He, Zhi-Yong; Chen, Jiang-Fan; Huang, Shi-Yuan; Liu, Bao-Hua; Liu, Hai-Xiao; Wang, Xiao-Tong
Abstract : Abstract: Numerous evidence suggests that RhoA/Rho kinase (ROCK) signaling pathway plays an important role in the pathogenesis of pulmonary arterial hypertension (PAH), but little is known about its effects on the development of PAH in mice with absence of the adenosine A2A receptor (A2A R). Eight A2A R knockout (KO) and 8 wild-type mice were used. Morphometric analysis of pulmonary arterioles included right ventricle/left ventricle plus ventricular septum (Fulton index), vessel wall thickness/total vascular diameter (WT%), and vessel wall area/total vascular area (WA%). The expression of RhoA and ROCK1 mRNA was determined by real-time polymerase chain reaction. The expression of RhoA, ROCK1, and phosphorylation of myosin phosphatase target subunit 1 proteins in pulmonary tissue was tested by Western blot. The position of ROCK1 protein was evaluated by immunohistochemistry. Compared with wild-type mice, A2A R KO mice displayed (1) increased Fulton index, WT%, and WA% ( P < 0.01); (2) increased mRNA expression of RhoA and ROCK1 (each P < 0.05); (3) increased protein expression of RhoA, ROCK1, and phosphorylation of myosin phosphatase target subunit 1 (each P < 0.01); (4) increased location of ROCK1 protein in endothelial and smooth muscle cells of pulmonary artery, bronchial, and alveolar epithelial cells. Activation of RhoA/ROCK signaling pathway may cause pulmonary vascular constriction, pulmonary artery remodeling, and PAH in adenosine A2A receptor KO mice.